Nature of technology and location effects on firm performance in the US medical device industry. Issue 5 (4th July 2019) - Rao-Nicholson, Rekha; Khan, Zaheer; Akhtar, Pervaiz
ABSTRACT: This paper examines the location effects on firm performance (sales, employment and market value) by analyzing geographical and technological proximities in the US medical device industry. The nature of technology is introduced as a new way to scrutinize the impact of various proximities, and the findings indicate that the geographical and technological proximity in itself does not affect performance, whereas the spatially-mediated technological proximity, characterized by the technological proximity within a cluster, positively influences the performance of medical device firms. The paper addresses an important theoretical question. It consequently contributes to the effects of different proximities and nature of technology on firm performance and provides relative managerial implications interlocked with insights obtained from the medical industry.